2022
DOI: 10.3311/ppar.18648
|View full text |Cite
|
Sign up to set email alerts
|

Airtightness of Nepalese Residential Buildings

Abstract: Experimental field measurements regarding airtightness following the fan pressurisation method were done on 25 typical residential buildings at different locations in Nepal. The field measurement data were classified according to building type and building age. The mean air permeability (Q50 ) for the studied buildings was 6.9 l/s·m2 and the mean air change rate was 55.5 air changes per hour at 50 Pa. The maximum air leakage rate (Q50 ) was 28.4 l/s·m2 for brick masonry in mud mortar type and the minimum recor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…For these reasons, ACH is high in classrooms. Table 7 summarises the ACH used to maintain the summer indoor temperatures found in previous studies [33,75,80,[95][96][97][98][99]. An ACH of 42-73 h −1 was found in a study conducted in traditional houses in Nepal for winter indoor thermal improvement during the day [75].…”
Section: Natural Ventilation In Terms Of Number Of Air Change Ratementioning
confidence: 98%
See 1 more Smart Citation
“…For these reasons, ACH is high in classrooms. Table 7 summarises the ACH used to maintain the summer indoor temperatures found in previous studies [33,75,80,[95][96][97][98][99]. An ACH of 42-73 h −1 was found in a study conducted in traditional houses in Nepal for winter indoor thermal improvement during the day [75].…”
Section: Natural Ventilation In Terms Of Number Of Air Change Ratementioning
confidence: 98%
“…An ACH of 42-73 h −1 was found in a study conducted in traditional houses in Nepal for winter indoor thermal improvement during the day [75]. According to a study conducted by Chaulagain et al [95] in twenty-five typical residential buildings in Nepal, an average ACH of 55.5 was obtained under natural ventilation at 50 Pa using the fan pressurisation method. Tong et al [80] found that natural ventilation could reach up to 91 ACH in a free-running room, which is suitable for maintaining indoor air temperature.…”
Section: Natural Ventilation In Terms Of Number Of Air Change Ratementioning
confidence: 98%